Medical expenditure of women during pregnancy, childbirth and puerperium at the beginning of China’s universal two-child policy enactment: a population-based retrospective study - Xin Wang; Ying Zhang; Yu Chen; Shuang Zang; Meizhen Zhao; Yalan Zhu (BMJ Open)
Objectives To describe and explore women’s medical expenditures during pregnancy, childbirth and puerperium at the beginning of the universal two-child policy enactment in China.Design Population-based retrospective study.Setting Dalian, China.Participants Under the System of Health Accounts 2011 framework, the macroscopic dataset was obtained from the annual report at the provincial and municipal levels in China. The research sample incorporated 65 535 inpatient and outpatient records matching International Classification of Diseases, 10th Revision codes O00–O99 in Dalian city from 2015 through 2017.Primary and secondary outcome measures The study delineates women’s current curative expenditure (CCE) during pregnancy, childbirth and puerperium at the beginning of the universal two-child policy in China. The temporal changes of medical expenditure of women during pregnancy, childbirth and puerperium at the beginning of China’s universal two-child policy enactment were assessed. The generalised linear model and structural equation model were used to test the association between medical expenditure and study variables.Results Unlike the inverted V-shaped trend in the number of live newborns in Dalian over the 3 studied years, CCE on pregnancy, childbirth and puerperium dipped slightly in 2016 (¥260.29 million) from 2015 (¥263.28 million) and saw a surge in 2017 (¥288.65 million). The ratio of out-of-pocket payment/CCE reduced year by year. There was a rapid increase in CCE in women older than 35 years since 2016. Length of stay mediated the relationship between hospital level, year, age, reimbursement ratio and medical expenditure.Conclusions The rise in CCE on pregnancy, delivery and puerperium lagged 1 year behind the surge of newborns at the beginning of China’s universal two-child policy. Length of stay acted as a crucial mediator driving up maternal medical expenditure. Reducing medical expenditure by shortening the length of stay could be a feasible way to effectively address the issue of cost in women during pregnancy, childbirth and puerperium.